PEMANFAATAN PERMAINAN LOMPAT ANGKA UNTUK MENGASAH KETERAMPILAN NUMERASI MATEMATIKA DI SDK NUBUNTAWA KOLOTOBO - Mariana Marta Towe (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
The low level of numeracy literacy in elementary schools, reflected in Indonesia's PISA mathematics score of 366, requires an innovative approach. This study focuses on the use of the educational game